Book Review of “Addiction Counseling Today: Substance and Addictive Behaviors” - Anderson, Murray (Canadian Journal of Counselling and Psychotherapy, 2021)
The issue of addictions and treatment has been increasingly prioritized by policy-makers in recent years, yet the meaning of the concept remains ambiguous. Throughout the 22 chapters of his book Addiction Counseling Today, Kevin G. Alderson weaves together the most salient theories, research, and therapies from the field of addiction and from contemporary developments in policy and practice. The book examines what the tenets of recovery and treatment mean in terms of not only the professional involved in providing treatment but also what recovery looks like for each client. Chapters cover the influence of ethics in treatment, theories of addiction, the neurosciences, and the recognition of behavioural addictions, including the controversies attached to the use of particular labels. A notable strength involves the author’s inclusion of the lived experiences of those who have dealt with various addictions. This book will be essential reading for practitioners, researchers, policy-makers, and students in the fields of addiction, social care, psychology, and criminal justice.